SUSTAINABLE PALM OIL AND RURAL LIVELIHOODS: CREATING SHARED VALUE TO SMALLHOLDERS AND COMMUNITIES (International Seven Journal of Multidisciplinary, 2025)
The palm oil industry's expansion has resulted in intricate social, economic, and environmental impacts on rural populations and small-scale farmers in producer nations. While palm oil contributes significantly to national economies, its conventional practices have been accused of raising concerns about ecological degradation, social exclusion, and inequitable benefit distribution. Creating Shared Value (CSV) has emerged as a strategic framework to align business objectives with community development. This research seeks to investigate ways sustainable palm oil initiatives can improve the well-being of rural communities by creating mutual benefits for smallholders and local groups. Employing a qualitative literature review method, this research systematically examines peer-reviewed articles, institutional reports, and empirical case studies published in the last decade. Data were collected through document analysis of at least 80 academic sources, managed using Mendeley Desktop. The dataset underwent thematic content analysis to reveal significant patterns and relationships associated with boosting economic empowerment, environmental stewardship, and social inclusion. The findings reveal that sustainable palm oil initiatives—particularly those involving ISPO/RSPO certification, inclusive business models, and multi-stakeholder collaborations—have improved smallholder incomes, reduced environmental impacts, and strengthened social capital. However, challenges such as high certification costs, insecure land tenure, and unbalanced gender participation persist. The study concludes that CSV-oriented palm oil systems offer promising pathways to sustainable development but require structural support, inclusive policies, and adaptive governance. Upcoming studies are encouraged to investigate the lasting impacts of CSV application and craft comparative case analyses across various agro-ecological zones and institutional frameworks.